Phonological Awareness Intervention and Basic Literacy Skill Development with Kiteracy-PiFo - Jadán-Guerrero, Janio (2020)
Phonological awareness refers to a global awareness of the sound structures of speech and the ability to manipulate those structures. Children with phonological awareness problems may have difficulty associating environmental sounds with appropriate objects and they generally do not play with sounds. This paper describes the manufacturing process of an educational kit to strengthen phonological awareness skills. Kiteracy-PiFo is a kit based on the literacy method Picto Phonic (PiFo), which is made up of one teddy bear with a built-in RFID reader and 30 tags that represent the letters of the alphabet. The kit was designed to carry out a longitudinal study in order to evaluate the effectiveness of interventions for children between 5 and 6 years old. In the manufacture of the kit participated 70 students, 5 from Computer Science Career, 20 from Digital and Multimedia Design Career, 45 from Psychology Career and 30 from Master in Education, mention Innovation and Leadership. All of them worked with 7 teachers who guided the development and intervention activities. A total of 25 kit were built, 5 of which were destined at 5 schools in Cartago-Costa Rica, 10 schools in Quito-Ecuador and 10 schools in Ambato-Ecuador. These kits were used to work on the development of phonological awareness with 667 children. © 2020, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.